2007
DOI: 10.1016/j.socscimed.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Doing participant observation in a psychiatric hospital— Research ethics resumed

Abstract: Social scientists who employ participant observation methods in medical settings are often held accountable for their research methods, specifically in regard to medical research ethics. However, the medical research ethics tradition rubs uneasily against participant observation and the anthropological understanding of the research process. The underlying premise for considering research ethics in the current case is the notion of the vulnerability of psychiatric patients as a participant group. Based on this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 30 publications
0
70
0
12
Order By: Relevance
“…In a Norwegian context, Øye et al equally pointed out that the psychiatric care and treatment are organized based on parallel psychodynamic notions of the patient as a weak, vulnerable and childlike subject (Oeye, Bjelland, Skorpen, & Anderssen, 2009). Furthermore Øye et al have shown that the underlying medical-ethical rationale in the psychiatric field in Norway is based on articulations of the patient as weak or vulnerable, because national policies for this field and the medical ethical committee system signal consent to this rationale (Oeye, Bjelland, & Skorpen, 2007). Overall, these studies point out that weakness works an inherent part of the classification of mental illness in Scandinavia.…”
Section: The Construction Of Mental Illness As a Matter Of Weaknessmentioning
confidence: 99%
“…In a Norwegian context, Øye et al equally pointed out that the psychiatric care and treatment are organized based on parallel psychodynamic notions of the patient as a weak, vulnerable and childlike subject (Oeye, Bjelland, Skorpen, & Anderssen, 2009). Furthermore Øye et al have shown that the underlying medical-ethical rationale in the psychiatric field in Norway is based on articulations of the patient as weak or vulnerable, because national policies for this field and the medical ethical committee system signal consent to this rationale (Oeye, Bjelland, & Skorpen, 2007). Overall, these studies point out that weakness works an inherent part of the classification of mental illness in Scandinavia.…”
Section: The Construction Of Mental Illness As a Matter Of Weaknessmentioning
confidence: 99%
“…Some patients were regarded as vulnerable with impaired decision-making capacity; therefore these patients were not asked for interviews. For further ethical considerations when doing participant observation involving psychiatric patients, see Oeye, Bjelland, and Skorpen (2007).…”
Section: Research Ethicsmentioning
confidence: 99%
“…The examples illustrate how questions raised by the Regional Committee of Medical Research Ethics became relevant for the experiences made in the study. They throw an interesting light on an emerging debate in qualitative research, which addresses the relevance of the medical ethics tradition in participatory research (Oeye, Bjelland, & Skorpen, 2007). …”
Section: Discussionmentioning
confidence: 99%